The endogenous protein content of ruminant proximal duodenal digesta - Bartram, Christopher Gordon (1987)
Protein arriving at the ruminant proximal duodenum consists of microbial protein, undegraded feed protein and endogenous protein. In this study, endogenous protein is defined as that fraction of the digesta derived from the animal itself (e.g. enzymes, plasma proteins, sloughed cells and mucus), not including any endogenous protein which may have been incorporated into the microorganisms.